Evaluating discovery tools in portuguese and spanish academic libraries - Rodríguez Bravo, Blanca (2014)
The aim of the research undertaken was to get to know the degree of implementation of discovery tools in university libraries in the Iberian Peninsula. It also allowed an initial evaluation of the facilities offered by the tools implemented. With regard to the presence of discovery tools we find a different situation in the two countries, with a higher degree of implementation in Spain. As for the behaviour of the discovery layers, the eight tools evaluated performed appropriately. Discovery tools represent a considerable advance. The combining of the library’s catalogue and indexes to articles with other sources of information in a single unified interface is an unquestionable improvement. However, catalogues and databases still fulfil some purposes better than discovery tools. Libraries need to consider their clients when putting up on their websites the various tools for gaining access to contents.